Analisis Pengaruh Harga Minyak Dunia, Pertumbuhan Ekonomi dan Pengeluaran Pemerintah Terhadap Pengangguran Dengan Inflasi Sebagai Variabel Moderating di Indonesia - A. Mahendra; Witya Shalini; Tohap Parulian; Ronnie Togar Mulia Sirait; Sever Ramapius Gulo (Journal on Education, 2022)
This research is intended to know the influence of world oil price, economic growth, and government expenditure on unemployem with inflation as moderating variables in Indonesia. Population in this research is Indonesia and 22 of them were selected to be the samples for this research through purposive sampling technique. Estimates conducted by the multiple regression analysis. The data that were used in this study were secondary data, consisted of World Oil Price, Economic Growth and Government Expenditure to Unemployemnt for the year 2000-2021. The results of this research, that Based on the partial test (t test), the World Oil Price, Economic Growth, and Government Expenditure have significant effect on the variables of the Unemployment in Indonesia, the simultan test (F test), World Oil Price, Economic Growth and Government Expenditure have a significant effect on the variables of the Unemployment. The inflation are unable to moderate the relationship between world oil price, economic growth and government expenditure on the unemployment.